World Bank Corporate Scorecard September 2012 : Integrated Results and Performance Framework - World Bank (World Bank, Washington, DC, 2017)
The corporate scorecard provides information on the Bank's overall performance and results achieved by its clients against the backdrop of global development progress. The scorecard facilitates dialogue between management and the board on progress made and areas that need attention. The four-tier scorecard covers the full spectrum of International Bank for Reconstruction and Development (IBRD) and International Development Association (IDA) activities. The corporate scorecard uses an integrated results and performance framework, which is organized in a four-tier structure that groups indicators along the results chain Two of the tiers track elements of development results (tiers one and two), and the other two capture elements of performance (tiers three and four). As the summary shows, the corporate scorecard monitors, at an aggregate level, whether the Bank is functioning efficiently and adapting itself successfully (tier four), and whether it is managing its operations and services effectively (tier three) to support countries in achieving results (tier two) in the context of global development progress and priorities (tier one). It presents a high-level view and is not intended to provide country or activity-level information.